Community Structure of Macroalgae in the Coastal Waters of Klui Beach, North Lombok - Ario Kusuma, Dipo; Japa, Lalu; Raksun, Ahmad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Macroalgae or also called seaweed are defined as macroscopic marine algae. This study aims to analyze the structure of macroalgae community in the coastal waters of Klui Beach, North Lombok. Samplings were conducted by using the combination of line transect and quadrat method. The macroalgae data collected were analyzed for calculating of species diversity index, eveness index, dominance index, and importance value index. The results showed that the community of macroalgae in the coastal water of Klui Beach consists of 11 species. The community of macroalgae of the coastal water of Klui Beach had species diversity index value of 1,661 (moderate category), evenness index value of 0,693 (relatively non-uniform category). However, the species dominance index value was 0,246 which indicates that there was no dominance species. Ulva intestinalis was the species with the highest importance value (81,93%). This species was also recorded as the highest density. Environmental protection efforts must be considered in the development of tourism areas for the sustainability of macroalgae community in the coastal waters of Klui Beach, North Lombok.